Child obesity prevalence across communities in New Zealand: 2010–2016. (4th March 2019) - Gibb, Sheree; Shackleton, Nichola; Audas, Rick; Taylor, Barry; Swinburn, Boyd; Zhu, Tong; Taylor, Rachael; Derraik, José G.B.; Cutfield, Wayne; Milne, Barry
Abstract: Objective : To assess community‐level differences in four‐year‐old obesity prevalence in New Zealand (NZ), trends over time, and the extent to which differences can be explained by ethnicity, deprivation and urbanicity. Methods: Obesity measures from the Ministry of Health's B4 School Check were available for 72–92% of NZ four‐year‐olds for fiscal years 2010/11–2015/16. Ethnicity, deprivation and urbanicity data for the 78 communities were obtained by linking to administrative records. Growth models were used to examine variability in obesity levels and trends over time, and the extent to which ethnicity, deprivation and urbanicity contributed to differences between communities. Results : There were large variations in obesity across communities (range 8.4% to 28.8%). A decline in the prevalence of childhood obesity was observed in most (48 of 78) communities from 2010/11 to 2015/16 (average change=0.2%, range=‐2.0% to 1.9%). Around 50% of the variance in obesity between territorial authorities could be explained by differences in socioeconomic deprivation and ethnic composition. Conclusions : Child obesity varies between NZ communities, but most territorial authorities have experienced a decrease in obesity over the period 2010/11–2015/16. Implications for public health : Addressing deprivation and ethnic inequalities in obesity could substantially reduce community‐level differences in obesity in NZ.